Effects of Degradation in Textolite Elements of Damaged Surge Arresters - Śmietanka, Hubert; Ranachowski, Przemysław; Ranachowski, Zbigniew; Wieczorek, Krzysztof; Kudela, Stanislav (Energies (Basel), 2022)
The aim of this work was to investigate the effects of the currents flowing through surge arresters on the internal insulating textolite structure. The samples were removed from high-voltage arresters that were taken out of service due to malfunction or failure. Discharge (short-circuit) currents of diverse intensities and durations caused degradation effects of varying degrees of advancement in the material of the tested elements. The samples were examined using microscopic methods. The use of the microanalysis technique EDS (energy-dispersive X-ray spectroscopy) made it possible to register changes in the elemental composition of the surface layer of the textolite materials, along with the intensification of the degradation effects. It was found that the high discharge current flows were subject to melting, charring and even burning of the organic adhesive. These effects caused serious changes in the content of elements in the top layer of the textolite and were the cause of a reduction in the service life, durability and reliability of the surge arresters. It was shown that the textolite materials had insufficient resistance to the effects of the emergency operation of the arresters after moisture ingress, which was a consequence of unsealing of the housing. A solution to this problem proposed by the authors could be the use of silicone elastomer as a covering of the textolite internal structure of surge arresters.